Interventions to address loneliness and social isolation in young people: A systematic review of the evidence on acceptability and effectiveness. (December 2021) - Osborn, Tom; Weatherburn, Peter; French, Rebecca S.
Abstract: Introduction: Loneliness is prevalent and associated with negative health outcomes in young people. Our understanding of how it can be best addressed is limited. This systematic review aims to assess the acceptability and effectiveness of interventions to reduce and prevent loneliness and social isolation in young people. Methods: Six bibliographic databases were searched; references of included studies were screened for relevant literature. A pre-defined framework was used for data extraction. Quality appraisal was performed using the Mixed Method Appraisal Tool. Data were synthesised narratively. Results: 9, 358 unique references were identified; 28 publications from 16 interventions met the inclusion criteria. The majority of interventions were high intensity, individual or small group interventions, often targeted at specific 'at risk' populations. While 14 interventions were associated with a statistically significant reduction in loneliness or social isolation, the heterogeneous measures of loneliness, small sample sizes, short periods of follow-up and high attrition rates limit evidence on effectiveness. Interventions implemented in more general populations of young people appeared more acceptable than those in specific 'at risk' populations. Conclusion: High intensity interventions are unlikely to be feasible at a population level. Further work is required to develop and evaluate theoretically-informed loneliness interventions for young people that reach wider audiences.